The relationship between physical activity and nutritional status and current blood glucose levels in diabetes mellitus sufferers at RSUP Dr. Wahidin Sudirohusodo Makassar - Nurbaiti, Nurbaiti (ScieClouds Publishing, 2023)
Diabetes Mellitus is a disease where there is an increase in glucose levels in the blood due to a lack of insulin. This disease is associated with hereditary factors, viruses, chemicals, unhealthy diet or lifestyle, lack of exercise, and being overweight or obese . The aim of this study was to determine the relationship between physical activity and nutritional status with blood glucose levels in diabetes mellitus sufferers at RSUP Dr. Wahidin Sudirohusodo Makassar. Type of non-experimental research with design Cross sectional study . The study population was all diabetes mellitus patients seeking treatment at Dr. Wahidin Sudirohusodo, the sample was 47 respondents who met the criteria. The collection technique uses accidental sampling . Data collection using questionnaires and observation sheets. The data that has been collected is processed and analyzed using computerization with appropriate tests. Data analysis includes univariate analysis and bivariate analysis using the chisquare test . Significance limit = 0.05, H0 is rejected if p < 0.05 and H0 is accepted if p > 0.05. The statistical test results showed a significant relationship between physical activity (p=0.001 < α 0.05) and nutritional status (p=0.001 < α 0.05) with instantaneous blood glucose levels. So the more regularly you do physical activity, the more normal your blood glucose levels will be and the better your nutritional status, the more normal your blood glucose levels will be.